2019
DOI: 10.1113/jp277306
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in left ventricular mitochondrial bioenergetics precede overt cardiac dysfunction and remodelling in Duchenne muscular dystrophy

Abstract: Key points Ninety‐eight per cent of patients with Duchenne muscular dystrophy (DMD) develop cardiomyopathy, with 40% developing heart failure. While increased propensity for mitochondrial induction of cell death has been observed in left ventricle, it remains unknown whether this is linked to impaired mitochondrial respiratory control and elevated H2O2 emission prior to the onset of cardiomyopathy. Classic mouse models of DMD demonstrate hyper‐regeneration in skeletal muscle which may mask mitochondrial abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 78 publications
(166 reference statements)
8
56
0
Order By: Relevance
“…Very recently, it has been demonstrated that mitochondrial impairment anticipates the onset of cardiomyopathy in a mouse model of DMD [42]. In particular, elevated mitochondrial H 2 O 2 emission and impaired oxidative phosphorylation have been detected in the left ventricle muscle of these mice at an early age, when signs of cardiac dysfunction are absent, suggesting that mitochondrial dysfunction plays a role in the etiology of the heart disease occurring at an older age [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, it has been demonstrated that mitochondrial impairment anticipates the onset of cardiomyopathy in a mouse model of DMD [42]. In particular, elevated mitochondrial H 2 O 2 emission and impaired oxidative phosphorylation have been detected in the left ventricle muscle of these mice at an early age, when signs of cardiac dysfunction are absent, suggesting that mitochondrial dysfunction plays a role in the etiology of the heart disease occurring at an older age [42].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress that is present in mitochondria from dystrophic hearts, increased PTP opening, and activation of caspase 9/3 reported in young mdx hearts before the onset of cardiac impairment are all suggestive of mitochondria-derived apoptosis [41] (Figure 3). A very recent study demonstrates that, during altered oxidative phosphorylation, complex I-sustained emission of mitochondrial H 2 O 2 increases in the left ventricle of dystrophin-deficient young mice, before any evidence of cardiac dysfunction [42]. Therefore, the identification of early mitochondria-specific impairments may lead to the development of mitochondria-targeted therapies able to recover respiratory chain activity and bioenergetic control, with the aim to delay the onset of cardiomyopathy and the consequent progression to heart failure in DMD.…”
Section: Mitochondrial Impairment/dysfunctionmentioning
confidence: 99%
“…Mitochondrial dysfunction plays a central role in numerous muscular disorders and pathologies, including DMD [38,39]. For example, work by Hughes et al (2019) demonstrated that mitochondrial dysfunction, attributed to impaired oxidative phosphorylation and elevated oxidant production, contributes to early stage pathology in the D2.mdx mouse model [40]. Additionally, in the mdx mouse model, mitochondrial dysfunction is one of the earliest cellular consequences of DMD and is associated with the impaired ability of dystrophic muscle cells to respond to sarcolemmal damage [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this investigation was to characterize SC-EVs and examine potential therapeutic benefits in vitro. Importantly, mitochondrial damage has been causatively linked to impaired SC function [18,19] and impaired mitochondrial function is known to play a role in muscle atrophy, and/or weakness occurring in muscular dystrophy [20][21][22], cancer cachexia [23], disuse atrophy [24,25], mechanical ventilation-induced diaphragm weakness [26][27][28][29][30], sarcopenia [31,32], and chronic kidney disease [33]. With the established links between SC function and mitochondrial function [34], we also investigated the extent to which SC-EVs could attenuate mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Hughes et al . (2020) investigated the remodelling of mitochondria energetics and cardiac dysfunction in Duchenne muscular dystrophy (DMD). Using the D2.B10‐DMD mdx /2J mice – an animal model that demonstrates skeletal muscle atrophy and weakness due to limited regenerative capacities and cardiomyopathy more akin to people with DMD – they discovered impairments in ADP‐stimulated respiration and ADP attenuation of H 2 O 2 emission.…”
Section: Remembering Jeremy Rice a Wonderful Colleague Gone Too Soonmentioning
confidence: 99%